The Conditions of Yemen and the Hijaz between the years (1907-1908): ‘Arab Independence’ Magazine as a Source - Mousa Abu-Mshnnk نور; Faour Al-Shraa إبراهيم فاعور (Mutah Journal of Humanities and Social Sciences (MJHSS), 2025)
This study examines the conditions of Yemen and the Hijaz between (1907-1908AD) through reports in the ‘Arab Independence’ magazine, which was published in French in Paris under the editorship of the Lebanese Najib Azoury. The study aims to provide a detailed analysis of the 15 issues of the magazine published between (April 1907 and June 1908AD), focusing on developments in Yemen and the Hijaz as covered in the magazine’s articles and reports by its correspondents. It employs a historical, descriptive, and analytical approach to present a clear picture of the political and social situation in the western part of the Arabian Peninsula. The magazine highlighted key issues such as the Hijaz Railway project and the conditions in the cities of Mecca and Medina. It also addressed the Yemeni Revolution of 1905 AD, shedding light on the harsh conditions faced by Yemenis due to injustice and persecution. Through this analysis, the study underscores the suffering of the people in these regions and shows how these events were part of the broader political and social movements in the early 20th century in the Arabian Peninsula